Compressive Strength Characteristics of Compressed Stabilized Earth Block (CSEB) Units and Walls - Bhatt, Toran Prasad (Journal of Engineering Technology and Planning, 2024)
This paper is mainly focused on compressive strength behavior of Compressed Stabilized Earth Block (CSEB) units and CSEB walls. Compressed Stabilized Earth Block (CSEB) is a rectangular block used in wall construction. The ingredients of CSEB are soil, cement, fine aggregate, crusher dust, and a small amount of water. These blocks have less energy consumption and carbon emission, and they provide improved thermal insulation. In addition, they use local resources and disseminate appealing aesthetics with elegant profile and uniform size. Due to these advantages CSEB can be used as a green construction material. This research aims to study the strength characteristics of CSEB wall in compression and evaluate the suitability of CSEB walls as load bearing walls in structures. This research studies physical and mechanical characteristics of CSEB units made from red residual soil of Lele (Lalitpur) with 8% cement for stabilization. This paper discusses the compressive strength behavior of walls constructed of size 0.660m x 1.100m x 0.220m using CSEB units in cement sand mortar and stabilized mud mortar separately which were tested after 28 days. The experimental values after laboratory testing of CSEB masonry wall with height to thickness ratio 5:1 for cement sand mortar (1:6) and stabilized mud mortar (stabilized with 8% cement and 16% extra sand) separately are compared with relevant values from different codes. Results obtained from compressive strength tests of masonry walls constructed in the laboratory and those values from different codes concerning the strength of masonry unit and mortar are compared and found to be in agreement. The comparison of laboratory results with codal provisions of design of masonry walls illustrate that CSEB masonry walls can be designed in the similar way as brick masonry walls.